2013
DOI: 10.7314/apjcp.2013.14.9.5513
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferation Effects of Interferon-gamma on Gastric Cancer Cells

Abstract: IFN-γ plays an indirect anti-cancer role through the immune system but may have direct negative effects on cancer cells. It regulates the viability of gastric cancer cells, so we examined whether it affects their proliferation and how that might be brought about. We exposed AGS, HGC-27 and GES-1 gastric cancer cell lines to IFN-γ and found significantly reduced colony formation ability. Flow cytometry revealed no effect of IFN-γ on apoptosis of cell lines and no effect on cell aging as assessed by β-gal staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
(45 reference statements)
2
16
0
Order By: Relevance
“…2 promoting cell apoptosis. IFNs could cause structural change of cell membrane and cytoplasm, DNA fragmentation and formation of apoptotic body; IFNs could upregulate TRAIL and FasL, and after conbined with corresponding receptor, is able to activate death domain structure that is associated with Fas, and induce apoptosis by activating downstream proteases, eg., Caspase -4 and Caspase -8 (Chawla-Sarkar et al, 2003;Guo et al, 2012;Dirican et al, 2013;Zhao et al, 2013;Laljee et al, 2013). 3 modulating immunological function.…”
Section: Discussionmentioning
confidence: 99%
“…2 promoting cell apoptosis. IFNs could cause structural change of cell membrane and cytoplasm, DNA fragmentation and formation of apoptotic body; IFNs could upregulate TRAIL and FasL, and after conbined with corresponding receptor, is able to activate death domain structure that is associated with Fas, and induce apoptosis by activating downstream proteases, eg., Caspase -4 and Caspase -8 (Chawla-Sarkar et al, 2003;Guo et al, 2012;Dirican et al, 2013;Zhao et al, 2013;Laljee et al, 2013). 3 modulating immunological function.…”
Section: Discussionmentioning
confidence: 99%
“…A study of gastric cancer suggested that IFN-γ might slow proliferation of some gastric cancer cells by affecting the cell cycle to play a negative role in the development of gastric cancer (Zhao et al, 2013). Corresponding to the present study, at 6 months after abrasion by both Pap smear and cryotherapy showed significant increased (p<0.001) IFN-γ and TNF-α mRNA expression, whereas the secreted IL-10 levels significantly decreased (p<0.001) in comparison with the base line at first recruitment as in Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies also have indicated that IFN-γ has the ability to directly inhibit cancer cell growth (Tate et al, 2012;Liu et al, 2012;Jin et al, 2013;Zhao et al, 2013;Wang, 2014); however, the mechanism remains unclear. Our present study demonstrated that the FADD/caspase 8/tBid/mitochondria pathway plays an important role in IFN-γ-induced apoptosis in the NSCLC cell lines H322M and H226.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ is a major activator of various types of immune cells (Wakita et al, 2009;Hayakawa et al, 2011) and also can induce the expression of the major histocompatibility complex in both normal and malignant cells and provokes inflammatory 1 infiltrate infiltration (Chen et al, 2012;Hong et al, 2014). In addition, IFN-γ can directly inhibit the growth of cells, in some cases, through the induction of cell cycle arrest with or without the concomitant induction of apoptosis (Tate et al, 2012;Liu et al, 2012;Jin et al, 2013;Zhao et al, 2013Wang, 2014. Recognition of the direct antiproliferative properties of IFN-γ and its ability to stimulate the immune system has led to the investigation of its therapeutic activity in a number of malignant conditions.…”
Section: Introductionmentioning
confidence: 99%